2015
DOI: 10.5152/anatoljcardiol.2015.6317
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Framingham risk and score models in predicting the presence and severity of coronary artery disease considering SYNTAX score

Abstract: Objective:Although various risk stratification models are available and currently being used, the performance of these models in different populations is still controversial. We aimed to investigate the relation between the Framingham and SCORE models and the presence and severity of coronary artery disease, which is detected using the SYNTAX score.Methods:The observational cross-sectional study population consisted of 227 patients with a mean age of 63.3±9.2 years. The patients were classified into low- and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…1 In research by Gunaydin et al (2016), it was found that HDL and family history had a significant implication for the incidence of high Syntax scores. 5 This is consistent with our study with significant association in family history and in HDL level for higher Syntax score ( Table 3).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…1 In research by Gunaydin et al (2016), it was found that HDL and family history had a significant implication for the incidence of high Syntax scores. 5 This is consistent with our study with significant association in family history and in HDL level for higher Syntax score ( Table 3).…”
Section: Resultssupporting
confidence: 93%
“…This is in line with the research conducted by Gunaydin et al (2016). 5 In the univariate analysis, it was found risk factors for family history and HDL levels showed significant differences. Previous studies revealed that low HDL was caused by increased proliferation of megakaryocyte progenitors and increased production of immature platelets in the bone marrow, thus the relationship between high MPV and low HDL could reflect the presence of an atherogenic and significant CHD.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The information included in the Framingham risk comprised the followings: age, gender, smoking status, systolic blood pressure, total and HDL cholesterol levels, the positive diagnosis of diabetes mellitus (DM) or the absence of diabetes, and the existence of hypertension (HT) under treatment or without medication. The total score revealed by the Framingham risk score allowed an estimation of a 10-year risk of developing coronary heart disease [1,2].…”
mentioning
confidence: 99%
“…A Turkish study of patients undergoing coronary angiography for the assessment of coronary artery disease (CAD) due to chest pain and ischaemia (n = 227), found that a FRF score calculated before angiography was in general predictive of the presence, extent and severity of CAD. The score was more predictive in patients with hypertension, obesity or a family history of the disorder and less predictive in male patients and in those with diabetes [53]. A large Iranian study (n = 46,674) reported the performance of the office-based version of the FRF in predicting fatal CVD events to be comparable with that of previously tested models [51].…”
Section: Box 1 Patient Populations Recommended For Plasma Lipid Screementioning
confidence: 87%